2016
DOI: 10.1186/s12885-016-2370-6
|View full text |Cite
|
Sign up to set email alerts
|

Safety and feasibility of fasting in combination with platinum-based chemotherapy

Abstract: BackgroundShort-term starvation prior to chemotherapy administration protects mice against toxicity. We undertook dose-escalation of fasting prior to platinum-based chemotherapy to determine safety and feasibility in cancer patients.Methods3 cohorts fasted before chemotherapy for 24, 48 and 72 h (divided as 48 pre-chemo and 24 post-chemo) and recorded all calories consumed. Feasibility was defined as ≥ 3/6 subjects in each cohort consuming ≤ 200 kcal per 24 h during the fast period without excess toxicity. Oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
222
2
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(240 citation statements)
references
References 27 publications
10
222
2
6
Order By: Relevance
“…Recently a series of studies in animal models have shown that periodic fasting (PF) lasting 2 or more days can be as effective as chemotherapy in delaying the progression of a wide range of cancers but, more importantly, can protect normal cells from the toxic effects of chemotherapy drugs while sensitizing cancer cells to the treatment (Raffaghello et al, 2008; Lee et al, 2012; Safdie et al, 2009; Dorff et al, 2016; Lee and Longo, 2011). A severely restricted diet that mimics PF started at middle age was effective in causing a major reduction in tumor incidence, in addition to delaying tumor onset and reducing the number of sites with tumor-like lesions, suggesting a reduction in metastatic cancers (Brandhorst et al, 2015).…”
Section: If and Health Indicators In Laboratory Animalsmentioning
confidence: 99%
“…Recently a series of studies in animal models have shown that periodic fasting (PF) lasting 2 or more days can be as effective as chemotherapy in delaying the progression of a wide range of cancers but, more importantly, can protect normal cells from the toxic effects of chemotherapy drugs while sensitizing cancer cells to the treatment (Raffaghello et al, 2008; Lee et al, 2012; Safdie et al, 2009; Dorff et al, 2016; Lee and Longo, 2011). A severely restricted diet that mimics PF started at middle age was effective in causing a major reduction in tumor incidence, in addition to delaying tumor onset and reducing the number of sites with tumor-like lesions, suggesting a reduction in metastatic cancers (Brandhorst et al, 2015).…”
Section: If and Health Indicators In Laboratory Animalsmentioning
confidence: 99%
“…In cases where cancer progression could be monitored, no evidence was found that fasting interferes with chemotherapy efficacy or protects the tumors (Safdie et al, 2009). In a dose-escalation study of 24–72 h of fasting prior to platinum-based chemotherapy in 20 cancer patients, IGF-1 levels decreased and 72 h of fasting was considered safe and feasible (Dorff et al, 2016). The results from a phase I clinical trial indicate that 72 h of PF in combination with chemotherapy were associated with normal lymphocyte counts and maintenance of a normal lineage balance in white blood cells, analogous to the PF effects on the murine immune system (Cheng et al, 2014; Safdie et al, 2009).…”
Section: Fasting and Its Clinical Efficacymentioning
confidence: 99%
“…An important role for ketone body-mediated protection was obtained from the study by Dorff et al [132] in which longer fasting duration prior to chemotherapy appeared more protective, yet only BHB, but not insulin, IGF-1 or glucose, were significantly different between 24 and 48 h of fasting prior to chemotherapy. This supports the hypothesis that KDs might be used as fasting-mimicking diets to reduce side effects from oxidative stress during prolonged treatment situations such as during several weeks of RT.…”
Section: Protection Of Normal Cells During Radiotherapymentioning
confidence: 99%
“…All of the preclinical studies summarized in table 1 have confirmed a reduction of side effects from a variety of chemotherapeutic drugs without interfering with, or even boosting, their anti-tumor effects. To date, 3 small studies in humans have also found evidence of a protective effect of STF against chemotherapy-related toxicity [130,131,132]. These studies and their relevance for patients receiving chemotherapy have been discussed in detail elsewhere [133,134,135,136] and will only briefly be reviewed here.…”
Section: Protection Of Normal Cells During Radiotherapymentioning
confidence: 99%
See 1 more Smart Citation